Стратегії балансування трафіку в кластері Kubernetes - Колтаков, О. А.; Савченко, Р. О. (ХНУРЕ, 2024)
Virtualization based on container technology is gaining more and more popularity due to its simplicity and convenience. Containerization technology provides users with more predictable, isolated, and lightweight runtime environments than traditional virtual machines. However, when the level of external traffic increases, the container cluster may experience a decrease in performance. In this work, an analysis of existing load balancing methods was carried out, their differences, shortcomings and application scenarios were given. The relevance of this work is due to the provision of effective load balancing in the container orchestration system, by analyzing existing traffic management models and algorithms for their further improvement
Keywords: kubernetes; балансування трафіку; кластер Kubernetes; трафік